Fetal alcohol spectrum disorders and their transmission through genetic and epigenetic mechanisms - Mead, Edward A.; Sarkar, Dipak K. (Frontiers in Genetics, 2014)
Fetal alcohol spectrum disorders (FASD) are a group of related conditions that arise from prenatal exposure to maternal consumption of the teratogen, ethanol. It has been estimated that roughly 1% of children in the US suffer from FASD (Sampson et al., 1997), though in some world populations, such as inhabitants of some poorer regions of South Africa, the rate can climb to as high as 20% (May et al., 2013). FASD are the largest cause of mental retardation in U.S. neonates, and ironically, are entirely preventable. FASD has been linked to major changes in the hypothalamic-pituitary-adrenal (HPA) axis, resulting in lifelong impairments through mental disorders, retardation, sensitivity to stress, and an impaired immune system with the related outcomes of elevated risk of cancer and other diseases. FASD arises from a complex interplay of genetic and epigenetic factors. Here, we review current literature on the topic to tease apart what is known in these areas particularly emphasizing the HPA axis dysfunction and how they tie into new studies of transgenerational inheritance in FASD.